Bio-fabricated CuO nanoparticles using Rhinacanthus nasutus leaf extract for antimicrobial and photocatalytic facets - M. Aswin; Prammitha Rajaram; Ambrose Rejo Jeice (Sustainable Chemistry for the Environment, 2025)
The increasing contamination of water sources poses a serious threat to clean water availability. Photocatalytic degradation offers a sustainable solution for wastewater treatment by utilizing light energy to break down pollutants without generating secondary waste. In this study, Rhinacanthus nasutus leaf extract serves as a green reducing and stabilizing agent for the eco-friendly synthesis of CuO bio-nanoparticles (BNPs). The bioactive compounds in the extract facilitate NPs formation while enhancing stability and functional properties. Various characterization techniques, including XRD, UV-Vis spectroscopy, FTIR, SEM-EDX, micro-Raman, and HRTEM analysis, were employed. The bio-fabricated CuO BNPs as monoclinic in crystalline structure with 19 nm size, and 1.61 eV band gap energy of CuO BNPs via UV–vis spectra and irregular spherical shape in morphology were found. The findings of the antimicrobial investigation demonstrated that the CuO BNPs caused the zones that were inhibitors to microorganisms as S. aureus, E. coli and A. flavus. Against three cationic dyes, Methylene Blue, Brilliant Green, and Rhodamine B, CuO NPs demonstrated photocatalytic activity, reaching degradation efficiencies of 92.86 %, 92.83 %, and 93.44 %, respectively.